Linking nutrient resorption stoichiometry with plant growth under long-term nitrogen addition - Aijun Xing; Haihua Shen; Longchao Xu; Mengying Zhao; Zhengbing Yan; Jingyun Fang (Forest Ecosystems)
Increased nitrogen (N) input can potentially lead to secondary phosphorus (P) limitation; however, it remains unclear whether differences in the plant's ability to cope with this P deficiency are related to their growth responses. Using a long-term experiment of N addition in a boreal forest, we explored the potential role of plant nutrient resorption efficiency and its stoichiometry in mediating plant growth responses to increased N input. We recorded the cover and measured the concentration and resorption efficiency of leaf N and P as well as the photosynthesis of a grass Deyeuxia angustifolia and a shrub Vaccinium vitis-idaea. The cover of the grass D. angustifolia increased with increasing N addition, while that of the shrub V. vitis-idaea decreased with N addition rate and almost disappeared from the high-level N addition over time. P resorption efficiency (PRE) increased in D. angustifolia but decreased in V. vitis-idaea with increasing leaf N:P which was increased by N addition for both species. In addition, photosynthesis increased linearly with N resorption efficiency (NRE) and PRE but was better explained by NRE:PRE, changing nonlinearly with the ratio in a hump-shaped trend. Furthermore, the variance (CV) of NRE:PRE for V. vitis-idaea (123%) was considerably higher than that for D. angustifolia (29%), indicating a more stable nutrient resorption stoichiometry of the grass. Taken together, these results highlight that efficient P acquisition and use strategy through nutrient resorption processes could be a pivotal underlying mechanism driving plant growth and community composition shifts under N enrichment.